Mutagenic Efficiency Of EMS And -Rays in Fenugreek (TRIGONELLA Foenum Graecum L.) - Mathur, V L; Sharma, G S (Annals of Arid Zone, 2016)
Seeds of fenugreek variety UM-75 were treated with three doses each of EMS and -rays. In M1 generation 40, 60 and 80 kR of -rays induced more cytomorphological damage than 0.4, 0.6 and 0.8% EMS. Normal appearing plants selected from each treatment were advanced to M2 generation. In M2 lowest concentration of EMS (0 (0.4%)generated maximum genetic variability for most of the traits. The estimates of heritability and genetic gain were also of higher order in this treatment.